X-Ray emission from SN1885A - Prucker, Marie; Sasaki, Manami; Schlegel, E.; Knies, Jonathan; Weber, Philipp; Kreykenbohm, Ingo; Wilms, Jörn (Astronomy & Astrophysics, 2025)
The historical supernova (SN) S Andromedae (S And or SN1885A) in the Andromeda Galaxy (M31) was discovered in August 1885 and since then has been studied extensively in multi-wavelength observations. Although the remnant of S And could be detected in optical images, so far no X-ray source has been reported at the position of S And. In this work we report the first detection of X-ray emission from the remnant of SN1885A with a significance of Ï = 3.43 using Chandra High-Resolution Camera (HRC) data taken in the imaging (I) mode. A total of 45 Chandra HRC-I observations were analysed, which corresponds to 940 ks of exposure time. A faint X-ray source could be detected at the reported position of the supernova remnant (SNR) 1885 and the corresponding X-ray luminosity in the 0.1 10 keV band was obtained. The resulting value from merging all 45 observations amounts to L0.110keV = (63+4) A- 1033 erg s1. To contextualise the results, the luminosity was compared to the X-ray luminosities of four of the oldest known X-ray SNe, some younger Galactic remnants, some SNRs in M31, and to theoretical predictions. The X-ray luminosity of SNR1885 is three to four orders of magnitude lower compared to the other examined remnants. A comparison to theoretical models shows that such low X-ray luminosities can only be produced if the ejecta is still expanding freely into a low-density interstellar medium (ISM). On the other hand, strong absorption by a high-density medium surrounding the freely expanding ejecta could also account for the lack of X-ray emission. Furthermore, the extremely low emission in X-rays could be an indication that the X-ray luminosity decreases faster towards the end of the ejecta-dominated (ED) phase in the evolution of SNRs than in the beginning.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Galaxies: individual: M31; ISM: supernova remnants; X-rays: individuals: S And; X-rays: individuals: SN1885A